Implementation of the 2013 Curriculum in Islamic Education in Elementary Schools - Efendi, Efendi; Wulandari, Viona Dwi; Rahmi, Azvi; Ratih, Nalar (Khalaqa: Journal of Education and Learning, 2024)
The implementation of the 2013 curriculum remains suboptimal, leading to challenges for PAI teachers in its preparation and execution. This study aims to describe how the 2013 curriculum is applied in PAI subjects within elementary schools. Utilizing a qualitative method with a descriptive approach, data collection involved observation, interviews, and documentation. The informants include Islamic Religious Education Teachers and School Principals, selected through these methods of observation, interview, and documentation. The data collected is analyzed qualitatively, following these steps: data reduction, presentation, conclusion, and verification. To ensure data validity, source triangulation and techniques were employed. The study findings indicate that (1) teachers prepare lesson plans by downloading templates from the Ministry of Education and Culture's website and adapting them to their school's context. (2) Teachers have not fully implemented integrative thematic learning, and their use of scientific learning approaches, media learning activities, and teaching methods remains conventional. (3) The evaluation of the 2013 curriculum in elementary PAI subjects shows that teachers employ authentic assessments to evaluate students' attitudes, knowledge, and skills.